Kaznačejstvo goroda Aššura-prolog imperii («Vozvraščenie k materi» = AMA-AR-GI4) - Jankovskaja, N.B. (Gs Diakonoff)
engl. Resümee: Aššur City Treasury as a Prolog to the Empire («Return to the Mother» = AMA-AR-GI4)